Coccidiosis among goats in Baghdad Province - Iraq - Ali Faraj, Azhar (The Iraqi Journal of Veterinary Medicine, 2006)
This study concerned with prevalence of infection of the goats and their kids with coccidia during the period from 1st March 2004 to 30th February 2005. Three hundred fifty two faecal samples were collected from 32 goats. The rate of infections in goats and kids was 47.6%, 61.1% respectively. The peak of infection was in spring and winter, and then the infection declined in hot and dry summer. The rate of infection in females (33.3%) was higher than in males (14.2%). Four species of coccidia were diagnosed Eimeria ahsata, Eimeria faurei, Eimeria pallida, and Eimeria ovinoidalis.